Transliteration System For Nepali Language - Shrestha, Suresh Man (Journal on Geoinformatics, Nepal, 2012)
Maps are one of the most popular and comprehensive documents in which people can see geographical names and are one of the most effective means to convey accurate place names. In absence of these names it would be very hard to relate the map with the ground. It is very important to standardize these names to get rid of confusion, inconsistency, uncertainty and misunderstanding the names presented in a map. It is rational to develop a Romanization (Transliteration) System for Nepali, not only to support the initiatives of United Nations Group of Experts on Geographical Names (UNGEGN) but also to standardize the way the Nepali geographical names are written especially in maps.